Whispers of Power: Representations of Female Agency in Sidney Sheldon’s Novels - Singh, Deeksha (Journal of Educational Research and Policies, 2026)
Sidney Sheldon’s The Sands of Time is a masterful tale of intrigue, romance, and resilience, featuring a cast of compelling female protagonists who navigate a world of political upheaval and personal transformation. This paper explores the nuanced portrayal of these captivating women, each shaped by fate, love, and the pursuit of power. From their initial vulnerabilities to their emergence as formidable figures, Sheldon crafts a narrative that transcends traditional gender roles, presenting heroines who embody strength, intelligence, and emotional depth. By analyzing the intricate layers of their character development, relationships, and struggles, this study highlights how The Sands of Time serves as a testament to the enduring power of women in literature. Through their whispered defiance and unyielding spirit, these characters not only shape their destinies but also redefine the boundaries of power and resilience in a male- dominated world.